THE IMPACT OF MATERNAL SECOND SIGNAL SYSTEM ACTIVITY ON MOTHER-CHILD INTERACTIONS DURING THE VERBAL DEVELOPMENT STAGE IN THE CONTEXT OF WAR AND HEALTH CRISES - Т. Знаменська; В. Луньов; Є. Зброжик; Л. Прудка; О. Жук (Неонатологія, хірургія та перинатальна медицина)
The transition from nonverbal to verbal communication in children is signifi cantly infl uenced by the maternal secondary signaling system. Current geopolitical and health crises, such as the war in Ukraine and post- COVID-19 syndrome, exacerbate maternal stress and may aff ect mother- child interactions and child development. Aim. The purpose of this study is to examine diff erences in the activity of the second signaling system between mothers who report diffi culties perceiving their children and those who do not, and to understand the impact of these diff erences on motherchild interactions during the child’s verbal developmental period. Materials and methods. The study involved 184 mothers, divided into two groups: 98 mothers who reported diffi culties in perceiving their children and 86 mothers who did not. The The Questionnaire for Assessing the Activity of the Second Signal System (Language and Cognitive Test: How Well Do You Understand and Communicate?) (Lunov, 2023) was used to evaluate the activity of the second signal system across eight subscales corresponding to diff erent cytoarchitectonic fi elds. Independent samples t-tests were conducted to compare the mean scores of each subscale and the overall integral index between the groups. Results. Signifi cant diff erences were found on all subscales and the integral index, indicating notable discrepancies in the activity of the second signaling system between the two groups. Mothers who reported diffi culties had consistently lower scores, highlighting the need for targeted interventions to support their communication and interaction with their children. Discussion. The fi ndings highlight the critical role of the second signaling system in maternal perception and interaction. The combined eff ects of war-induced trauma and post- COVID-19 syndrome exacerbate these challenges and underscore the need for comprehensive support programs. Findings from studies underscore the importance of addressing transgenerational attachment factors and maternal mental health to improve mother- child relationships and promote healthy developmental outcomes.